Cubebin: A Small Molecule with Great Potential - Rocha Pissurno, Ana Paula da [UNESP]; laurentiz, Rosangela da Silva de [UNESP] (Brazilian Chemical Soc, 2017)
The (-)-cubebin is a lignan dibenzylbutyrolactolic of occurrence in various species of plants, especially in the genus Piper. Although it has been known for over 150 years, the last few decades the biological properties of this molecule has attracted the attention of several research groups. Recent publications obtained from Scopus bases, SciFinder and PubMed database have highlighted the numerous biological activities attributed to cubebin, as trypanocidal activity, shistomicida, cytotoxicity on cancer lines, vasodilator, antihistaminic, and anti-inflammatory. These studies demonstrate the pharmacological potential of cubebin and its importance as starting material to obtain even more potent derivatives.
Keywords: Natural product; erectile dysfunction; cubebin; biological properties